COMA PATIENT MONITORING USING BRAIN COMPUTER INTERFACE - A., Manonmani; M., Arivalagan; M., Lavanya; S., Sellakumar (International Journal of Psychosocial Rehabilitation, 2020)
This work is based on the coma patient movement and monitoring system, which is the system that is used to detect movement changes in the coma patient. This paper presents the method of patient movement monitoring system for those patients that are taking medical treatment in both local and foreign hospitals with the help of the frame comparison approach. Coma lies on a spectrum with other alterations in consciousness. The level of consciousness required by, for example, someone in this passage lies at one extreme end of the spectrum, while complete brain death lies at the other end of the spectrum. The healthcare industry has perpetually been at the forefront in the adoption and utilization of information and communication technologies (ICT) for efficient healthcare administration and treatment. Recent developments in ICT and the emergence of the Internet of Things (IoT) have opened up new avenues for research and exploration in all fields, including the medical and health care industries. Hospitals have started using the cell instruments for communication intent, and for this intent, the internet of things (IoT) has been used and fused with wi-fi sensor nodes reminiscent of and small sensor nodes. In this paper, novel methods to utilize the IoT within the field of scientific and crafty wellness care are presented. The majority of the survey exists about the different health care approaches used in the IoT, similar to wireless well-being monitoring, U-healthcare, e-healthcare, and age-friendly healthcare techniques.